Interaction between Dectin-1 gene polymorphisms and low weight on the risk of invasive pulmonary aspergillosis in patients with lung cancer undergoing surgery - Wenfang Jin; Yu Yao; Yanling Lv (Discover Oncology)
Abstract The aim of this study was to investigate the impact of four single nucleotide polymorphisms (SNPs) within the Dectin-1 gene, the interaction between SNPs of the Dectin-1 gene and the low weight on susceptibility to invasive pulmonary aspergillosis (IPA) in patients with lung cancer undergoing surgery. Logistic regression was used to test the relationship between four SNPs of the Dectin-1 gene and IPA susceptibility. The generalized multifactor dimensionality reduction (GMDR) model was used to assess the interaction between SNPs of Dectin-1 gene and low weight. We found that both the rs3901533-TT and the rs3901533-TT or GT genotype were associated with an increased risk of IPA, the adjusted ORs (95% CI) were 1.98 (1.37–2.62) (TT vs. GG) and 1.43 (1.10–1.81) (GT+TT vs. GG), respectively. We also found that rs7309123-GG and rs7309123-GG+CG genotypes were associated with an increased risk of IPA, adjusted OR (95% CI) were 2.06 (1.43–2.71) (GG vs. CC), 1.63 (1.15–2.12) (CG+GG vs. CC), respectively. GMDR model found a statistically significant two-dimensional model combination (including rs3901533 and low weight). The participants with rs3901533-GT or TT genotype and low weight had the highest risk of IPA, compared to participants with rs3901533-GG genotype and without low weight, OR (95% CI) was 3.24 (1.68–4.92) (p < 0.001). In conclusion, rs3901533 and rs7309123 of Dectin-1 gene, the interaction between rs3901533 and low weight were correlated with increased risk of IPA in patients with lung cancer undergoing surgery.